The Transcriptional Aftermath in Two Independently Formed Hybrids of the Opportunistic Pathogen Candida orthopsilosis - Hovhannisyan, Hrant (mSphere, 2020)
Interspecific hybridization can drive evolutionary adaptation to novel environments. The Saccharomycotina clade of budding yeasts includes many hybrid lineages, and hybridization has been proposed as a source for new pathogenic species. Candida orthopsilosis is an emerging opportunistic pathogen for which most clinical isolates are hybrids, each derived from one of at least four independent crosses between the same two parental lineages. To gain insight into the transcriptomic aftermath of hybridization in these pathogens, we analyzed allele-specific gene expression in two independently formed hybrid strains and in a homozygous strain representative of one parental lineage. Our results show that the effect of hybridization on overall gene expression is rather limited, affecting ∼4% of the genes studied. However, we identified a larger effect in terms of imbalanced allelic expression, affecting ∼9.5% of the heterozygous genes in the hybrids. This effect was larger in the hybrid with more extensive loss of heterozygosity, which may indicate a tendency to avoid loss of heterozygosity in these genes. Consistently, the number of shared genes with allele-specific expression in the two independently formed hybrids was higher than random expectation, suggesting selective retention. Some of the imbalanced genes have functions related to pathogenicity, including zinc transport and superoxide dismutase activities. While it remains unclear whether the observed imbalanced genes play a role in virulence, our results suggest that differences in allele-specific expression may add an additional layer of phenotypic plasticity to traits related to virulence in C. orthopsilosis hybrids. IMPORTANCE How new pathogens emerge is an important question that remains largely unanswered. Some emerging yeast pathogens are hybrids originated through the crossing of two different species, but how hybridization contributes to higher virulence is unclear. Here, we show that hybrids selectively retain gene regulation plasticity inherited from the two parents and that this plasticity affects genes involved in virulence.